EFEK PEMBERIAN Morinda citrifolia,L PADA KADAR TGF-Β SERUM DAN EKSPRESI KOLAGEN PADA GINJAL TIKUS DIABETES NEFROPATI - Arya Iswara; Udadi Sadana; Indranila Kustarini (Universitas Muhammadiyah Semarang, 2014)
Background: Morinda citrifolia L contain components that lowering the oxidative stress andthe ability to regenerate the renal function through the measurement of renal extra cellularmatrix and growth factor. The detection from renal functions remission can be measuredthrough the transforming growth factor beta (TGF-β) level, and collagen deposition. Aims: This experiment was to prove the Morinda citrifolia L effect to lowering the TGF-β level andcollagen deposition in streptozotocin-induced nephropathy diabetic Sprague Dawley rats.Method: The post test only control group design experiment in thirty rats randomized intopositive control group and four treatment group and induced with streptozotocin in 40mg/kgWBdoses. The rats treated with Morinda citrifolia extract which was divided into four doses(10;20;40;80mg/dL) then determine TGF-β level and collagen deposition. The data analyzedusing SPSS ver 17 with oneway-ANOVA and post hoc LSD, Kruskal-Wallis and Mann-WhitneyU and Spearman’s Rho with confidence interval 95% (p<0,05). Result: The statisticallyanalysis from rats treated with morinda extract resulted a significant result in TGF-β level, correlation between TGF-β level and collagen deposition (p<0,05). Conclusion: Morindacitrifolia treatment can substantially improve the activity of the renal function, shown by lowerTGF-β level and better density of collagen deposition compared with control group and 10-20mg/dL morinda treatment dose showed the best result.Keywords: Nephropathy diabetics, Morinda citrifolia, TGF-β level and collagen deposition.